Decoding the Workplace - Ballard, John (Ascent Audio, 2018)
This highly readable career development book reveals dynamic aspects of the workplace that are hidden to many, ignored by others-factors that can make or break careers. - Provides easy-to-read information that allows readers to better understand the workplace around them, the behavior of others, and even themselves - Offers proven advice that can help readers be more effective, regardless of what stage they are in their careers - Discusses fifty keys for unlocking the workplace and illustrates key concepts through dozens of stories and practical examples - Presents insights grounded in what management scholars know about human behavior, management, and the workplace.